KORELASI AKTIVITAS BELAJAR DARING TERHADAP HASIL BELAJAR SISWA KELAS IVB SDN 11 PONTIANAK KOTA - Katarina Yuliyanti; Budiman Tampubolon; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the performance between online learning activities and student learning outcomes of class IVB elementary school 11 Pontianak Kota. Using descriptive research methods, the form of interrelationship studies by way of correlation studies. This study is a population study with a total of 26 students. Data collection tools in the form of questionnaires and documentation of the average value of PAS. The results showed that there were online learning activities, 8 students in the high category, 8 people in the medium category, and 10 people in the low category. While student learning outcomes at the average value of thematic PAS were 0 students in very good category, 11 students in good category, 10 students in enough category, and 5 students in poor category. The result r count 0.392 while r table 0.388 means r count> r table. Based on the research results, the relationship between online student learning activities and the learning outcomes of fourth grade students of elementary school 11 Pontianak City is categorized as low.Keywords: learning activity, correlation, and learning outcomes.